Investor Sentiment and Stock Return Volatility: Implication of The Israel-Palestine Conflict on Sharia Stocks in Indonesia - Setianingsih, Hesti Eka; Fauziyah, Nurul; Hasyim, Fuad (Universitas Islam Internasional Indonesia, 2024)
The escalation of the Israel-Palestine conflict has garnered global attention. Public condemnation through mass boycotts of pro-Israel products has significantly impacted capital markets, particularly the sharia stock market in countries with Muslim majority populations. The volatility of sharia stock returns becomes a crucial focal point in this context as it serves as a sensitive indicator of geopolitical events and changes in investor sentiment. This study investigates the connection between the volatility of sharia stock returns in Indonesia and investor sentiment as a result of the Israel-Palestine conflict. Researchers use the GARCH (1,1) model to look at how investor sentiment and the conflict between Israel and Palestine affect the volatility of Sharia stock returns indexed by the Jakarta Islamic Index (JII), using monthly data from January 2012 to February 2024. The researchers hypothesized that investor sentiment and the Israeli-Palestine conflict affect Islamic stock returns in Indonesia, but the results of this study show that the two factors have no effect on Islamic stock returns. The findings of this research provide valuable insights for financial market practitioners, investors, and regulators in understanding the impact of geopolitical conflicts on the capital market, particularly in the context of sharia stocks in Indonesia. By considering investor sentiment factors and market fluctuations triggered by such geopolitical events, this study provides a stronger foundation for wise investment decision-making and effective risk management, thereby enhancing the stability and performance of sharia capital markets in the future.